2010
DOI: 10.3141/2180-05
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Workability and Compactability of Warm-Mix Asphalt

Abstract: One of the main benefits advertised about the use of warm-mix asphalt is the increased workability at conventional and lower compaction temperatures. From a field perspective, “workability” is commonly defined as the asphalt mixture property that describes the ease with which the asphalt mixture can be placed, worked by hand, and compacted to the desired mat density. Unfortunately, a laboratory property and test condition have yet to be developed to quantify these field characteristics. A research effort to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 1 publication
1
55
0
Order By: Relevance
“…Bhargav (2013) found that minimum air voids of mixtures with 1.5%, 2% and 2.5% Rediset occurred at 1208C as a compaction temperature. In other studies, it was observed that air voids of Marshal samples decreased as Rediset content increased (Bennert et al 2010). Lee and Kim (2009) found that the bulk specific gravity of mixtures containing Rediset (prepared for indirect tensile strength test) were higher than those mixtures containing Sasobit w , Advera, Asphamin, Cecabase and Evotherm.…”
Section: Volumetric Propertiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Bhargav (2013) found that minimum air voids of mixtures with 1.5%, 2% and 2.5% Rediset occurred at 1208C as a compaction temperature. In other studies, it was observed that air voids of Marshal samples decreased as Rediset content increased (Bennert et al 2010). Lee and Kim (2009) found that the bulk specific gravity of mixtures containing Rediset (prepared for indirect tensile strength test) were higher than those mixtures containing Sasobit w , Advera, Asphamin, Cecabase and Evotherm.…”
Section: Volumetric Propertiesmentioning
confidence: 93%
“…Bennert et al (2010) reported that that addition of 1% Rediset in a PG76-22 has no effect on the recovery percentage and nonrecoverable creep compliance (J nr ), while 2% Rediest content increased the J nr and decreased the percentage of recovery in the multiple stress creep and recovery test (MSCR) at 648C. It implies that Rediset content may have an effect on the high temperature properties of an asphalt binder.…”
Section: Effect Of Rediset At High Temperaturesmentioning
confidence: 94%
See 3 more Smart Citations